An alternative to hysterectomy in the treatment of excessive uterine bleeding - Zimmer, Mariusz; Rosner-Tenerowicz, Anna; Wiatrowski, Artur; Sysło, Piotr (Menopause Review/Przegląd Menopauzalny, 2008)
Excessive uterine bleeding is experienced by 10-70% of woman of reproductive age. In some cases it is dysfunctional uterine bleeding (DUB). DUB is diagnosed by excluding other possible causes of uterine bleeding: abnormal uterine bleeding (AUB). However, the most frequent causes of excessive uterine bleeding are anatomical changes, which can include: fibroids, adenomyosis, endometrial polyps, and hyperplasia of the endometrium. There are many methods of treatment of excessive uterine bleeding. Nearly half of patients cannot be cured with oral or injected medicaments because of their inefficiency or intolerance. We should consider use of the intrauterine system releasing progestogen in these cases. This way of treatment is a new, effective alternative to endometrial ablation or hysterectomy.